COMPARISONAL ANALYSIS OF STUDENTS' LEARNING ACHIEVEMENTS FROM IBTIDAIYAH ELEMENTARY SCHOOL AND MADRASAH IN LEARNING ISLAMIC RELIGIOUS EDUCATION AT SMP NEGERI 4 RANTAU ACEH TAMIANG REGENCY - Aini Safitri (The Islamic Education and Multiculturalism Foundation, 2021)
Abstract: This study discusses the comparison of student achievement from Elementary Schools and Madrasah Ibtidaiyah in learning Islamic education at State Junior High School 4 Rantau, Aceh Tamiang district. The research conducted by the author uses a qualitative approach that is a field study of Islamic religious education learning and analyzes student achievement from two different backgrounds. The use of the method in this study is a qualitative descriptive method. Data collection is done by observation, interviews, documentation (notes or archives). Data analysis techniques include data reduction, data presentation, data verification and critical analysis. The results showed that students from both different backgrounds obtained good learning scores, good skills, and were able to apply good attitude values ​​and uphold ethics in learning.